Constructing Netlike Nanosheets of ZnO/BiOCl with Heterojunction as Robust Material for Electrochemical Amine Detection. Issue 1 (14th November 2022) - Ahmed, Maruf; Zhao, Ruihua; Xing, Tian; Du, Jianping
Abstract: The electrochemical sensing is a potential method for detection of trace toxic substance. Herein, the heterojunction of netlike ZnO/BiOCl nanosheets was constructed for the enhanced electrochemical detection of ammonia. Cyclic voltammetry and linear sweep voltammetry were used to investigate the electrochemical performance. The results show that the ZnO/BiOCl‐modified electrode exhibits higher sensitivity towards ammonia compared with the ZnO and BiOCl‐based electrodes, which is ascribed to band structure and fast electron transfer. The high response of 11.8 μA mM −1 and a low detection limit (LOD) of 0.25 μM are achieved. In addition, the ZnO/BiOCl material exhibits high selectivity, repeatability and stability. The better linear relationship between concentration and current ( R 2 =0.99) is significant for quantitative detection of ammonia, implying that netlike ZnO/BiOCl nanosheets can serve as electrochemical sensing platform for detecting toxic substance. This research provides a strategy for fabricating two‐dimensional netlike materials and regulating heterojunctions used for electrochemical application. Abstract : ZnO/BiOCl heterojunction material is fabricated by constructing netlike ZnO and BiOCl nanosheets. It exhibits high selectivity to ammonia and detection limit is 0.25 μM, which is suitable to detect volatile amines quantitatively. The synergetic effects of the heterojunction and netlike structures contribute to boosting electrochemical activity. The ZnO/BiOCl hybrid could be an promising candidate for detection and analysis.